The Role of Personal Values and Student Achievement in Academic Dishonesty - Koscielniak, Maciej; Bojanowska, Agnieszka (Frontiers in Psychology, 2019)
Although multiple individual and environmental causes of students’ dishonest behaviors have been well documented in past research, not much attention has been paid to the human values perspective yet. The current study investigates the direct relationship of values with academic dishonesty, as well as the moderating role of students’ past achievements (grades). Analyses were performed on 219 Polish university students (M = 46, F = 173). Questionnaire measures were used, including Schwartz’s Portrait of Values Questionnaire (PVQ). It was found that socially orientated human values (Conformity, Tradition) were negatively related to unethical behaviors, while personally focused values (Hedonism, Power, Stimulation) correlate positively. Additional analyses revealed that the relationships of some values (Achievement and Security) with academic dishonesty are significantly moderated by students’ academic performance (grades). In the discussion we suggest that academic dishonesty is a pattern of behavior that can be successfully investigated from the perspective of human values – in order to identify its correlates and to plan preventive actions.